Prevention of chronic furunculosis with low-dose azithromycin - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2007)
Background: Chronic furunculosis is a recurrent staphylococcal abscess of the hair follicle. Besides ensuring personal hygiene, the management consists of long-term treatment with topical and systemic antibiotics. Objective: An open-labeled, prospective study was conducted to assess the clinical and in vitro efficacy of azithromycin in the long-term suppressive treatment of chronic furunculosis. Methods: Patients with a history of three or more episodes of furuncles were assigned to receive 12 weeks of suppressive treatment with azithromycin at a weekly dosage of 500 mg. In vitro susceptibility of azithromycin was evaluated with E-test. The primary efficacy parameter was complete absence of furuncles during the 3 months of azithromycin treatment. The secondary efficacy parameter was further absence of furuncles during the 3-month follow-up period. Results: At the end of 3 months of therapy, azithromycin was found to be effective in 19 (79.2%) of 24 patients; 18 of these patients remained in remission during the 3 months of follow-up. All of the strains were methicillin-sensitive. The results of the E-test showed that 15 of 18 strains (83.3%) were susceptible to azithromycin. Conclusion: The results of this study indicate that azithromycin is an effective and safe alternative in the treatment of chronic furunculosis caused by methicillin-sensitive Staphylococcus aureus.
Keywords: azithromycin; chronic furunculosis; E-test; Staphylococcus aureus; suppressive treatment; SKIN; PROPHYLAXIS; INFECTIONS